The Most Frequently Used Techniques In Teaching English Speaking at High Schools - Nur Qolbi Rustan; Rusdiana Junaid (Jurnal Studi Guru dan Pembelajaran, 2024)
Teaching English with an appropriate technique can improve students speaking skills. This research aims to find out the most frequently used techniques in teaching English speaking at High Schools in Palopo. The main discussions were divided into two sub-focus of research questions, namely 1) What are the most frequently used techniques in teaching speaking English at High Schools in Palopo? 2) What are the problems faced by teachers in teaching speaking English at High Schools in Palopo? This type of research was classified as qualitative with the research approach used as a descriptive analysis. The research subjects of this study were 21 English teachers, the teachers at Junior High Schools, and Senior High Schools. Furthermore, the methods used in collecting the data were observation, in-depth interviews, and reference resources. Then, the data processing and data collection techniques were carried out in three stages, namely: data reduction, data display, and conclusion. The data were collected by using the WhatsApp app and Google Forms. The results of this study indicate that the techniques most often used in teaching speaking English at Palopo High Schools were: Role Play, Discussion and Debate, and Information Gap. Meanwhile, some of the challenges faced by teachers when teaching English, include 1) Lack of vocabulary, 2) Lack of confidence, 3) Mispronunciation, 4) Lack of facilities, and 5) Lack of motivation. The recommendation of this research was: 1) students should be abler to be motivated by the various techniques in learning English speaking. 2) As professional educators, the teachers should prepare themselves to use enjoyable techniques so that the students will focus on learning.